Display controller and circuit modeling for a new electronic paper display technology - Serti, Tomas; Petrichos, Nikolaos (My University, 2017)
Reflective display technologies have gained popularity in recent years and have found use in many applications. As such, a lot of research has been conducted to find new such technologies and improve upon current ones. The Rdot display technology is an advancement on reflective electronic paper displays by adding natural color without compromising on image quality. In this thesis the Rdot technology is evaluated and modelled electrically through an analog circuit simulations using discrete electronic components. These circuit models are compared with other similar circuits of similar technologies and it is determined whether it is possible to use similar driving schemes to drive a multipixel Rdot display. Timing and voltage information is also derived from the circuit simulations. A digital display controller design is also proposed and realized on an FPGA, written in VHDL. The necessary digital components are noted and the system block diagram as well as the individual blocks with the signals between them are shown. In addition to the digital design, the necessary peripheral driving circuits and their configuration are described. It is noted that the use of DACs is obsolete in this design and the display can be driven with the same 1V source as the logic circuits.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science